LRP11 facilitates lipid metabolism and malignancy in hepatocellular carcinoma by stabilizing RACK1 through USP5 regulation - Litao Liang; Wenbo Jia; Jinyi Wang; Yanzhi Feng; Deming Zhu; Wenhu Zhao; Chao Xu; Xiangyu Ling; Qingpeng Lv; Xiaoming Ai; Lianbao Kong; Wenzhou Ding (Molecular Medicine)
Abstract Hepatocellular carcinoma (HCC) is one of the most prevalent cancers worldwide and a major public health challenge. Lipid metabolism plays a crucial role in the metabolic reprogramming observed in HCC, although the underlying mechanisms are still being elucidated. Nile red staining and lipid assays showed that LRP11 knockdown significantly reduces lipid accumulation in HCC cells, with a concurrent decrease in key lipid metabolism markers such as FSAN, ACLY and ACSL4, as demonstrated by Western blotting. Mass spectrometry (MS) and co-immunoprecipitation (Co-IP) revealed that LRP11 recruits USP5, enhancing USP5-mediated deubiquitination of RACK1. Truncation analysis identified LRP11 residues 309–500 as critical for interaction with the RACK1 residues 91–231. These findings suggest that LRP11 may influence lipid metabolism and progression in HCC through USP5-mediated stabilization of RACK1. Based on these results, LRP11 emerges as a potential target for further exploration in HCC therapy. Targeting LRP11 or disrupting its interactions with USP5 or RACK1 could offer new avenues for treatment, though additional research is required to validate these therapeutic possibilities.